ANALISIS USER EXPERIENCE PENGGUNA APLIKASI NEOBANK BERDASARKAN ALAT UKUR HEART METRICS - Ratih Aisyah; Annisa Lusyani Zahra; Dwi Shahita; Wafi Hidayatullah (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Based on the accumulated reviews, it is known that the symptoms of disrupted user experience are supported by several reviews which show dissatisfaction in operating the Neobank application, which may have an effect on decreasing user satisfaction. This problem is something that must be monitored by PT. Neo Commerce Bank so that the Neobank application remains sustainable. This research has a mission to find out what will be emphasized for the development of the Neobank application based on the HEART Metrics measurement tool with the method implemented is Importance Performance Analysis. Determining the number of respondents in this study implemented the formula created by Slovin and obtained a population of 99 respondents who are residents of the island of Java who use the Neobank application. Until the results of the importance and performance elaboration, there are several statement items that need to be evaluated, but there are items that need to be evaluated and prioritized immediately based on the results of the calculation of the suitability level and Cartesian diagram, namely the user experience that it is not uncommon to experience errors when operating a Neobank with a level conformity 91.91%. The items in the aforementioned statement have the potential to divert the user experience in using the Neobank application.